A Hybrid Encryption and Decryption Algorithm using Caesar and Vigenere Cipher - Tan, Camille Merlin S.; Arada, Gerald P.; Abad, Alexander C.; Magsino, Elmer R. (Journal of physics. Conference series, 2021)
This paper presents a hybrid encryption and decryption algorithm, which combines the concept of Caesar Cipher and Vigenere Cipher algorithms. This was done by comparing the proposed design with some of the well-known ciphers such as Hill Cipher, Caesar Cipher and Vigenere Cipher through MATLAB simulations. Parameters such as letter frequency and graph behavior were evaluated. Results show that the proposed algorithm performs excellently. It has the most evenly distributed graph among other ciphers being compared in terms of their frequency of the ciphertext. Also, the decryption algorithm was able to achieve 99.99% accuracy.